轴对称载荷作用下的旋转薄壳类零件的应力分析 - 梁治国; 吴春英; 王宁侠 (Jixie chuandong)
On the basis of the stress distribution of the rotary thin shell parts under the symmetrical axial loads, the characteristics of stress distribution for the several typical thin shell parts are put forward and the simple design approach to the shell parts with the uniform shear stresses is presented.